ANALISIS PENGARUH DISIPLIN KERJA, PENGALAMAN KERJA, UPAH DAN UMUR TERHADAP KINERJA KARYAWAN INDUSTRI KREATIF - Zandra Dwanita Widodo; Sri Wijiastuti; Rini Adiyani; Syahri Al Husin; Darsono Darsono; Abdullah Zailani (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to analyze the effect of work discipline, work experience, wages and age on improving the performance of creative industry employees at Ndalem Kaos Production Sukoharjo, Central Java, Indonesia. In achieving the objectives of this study, researchers used quantitative research methods. Improved employee performance can be optimized in terms of efficiency and effectiveness of the production process from time to time. Optimizing employee performance is an important element in the company that must be considered. The company always strives to optimize employee performance and realize the company's vision and mission. Data collection in this study used a questionnaire which was distributed directly to 40 respondents at Ndalem Kaos Production in Sukoharjo, Central Java. The results of this study show that the variables of work discipline, work experience and wages have a significant and positive effect on the productivity of creative industry employees, Ndalem Kaos Production in Sukoharjo, Central Java. Meanwhile, the age variable has no significant effect on the productivity of the Ndalem Kaos Production creative industry employees in Sukoharjo.